Lament: Homiletical Groans in the Spirit (Homiletic, 2009)
The expression of celebration has been the normative discussion point in African American homiletical theory to the neglect of the expression of lament. This is not to say that lament has not been practiced in the pulpit or beyond but it is to claim that lament has not been named as a viable sermonic expression as has been done with celebration; thus, lament has been silenced in homiletical discussions. In light of this, this article aims to highlight lament and argue that it is a critical manifestation of the Spirit in preaching and should be voiced alongside celebration.